Conformational Substates of Amyloidogenic hIAPP Revealed by High Pressure NMR Spectroscopy. Issue 12 (9th August 2016) - Erlach, Markus Beck; Kalbitzer, Hans Robert; Winter, Roland; Kremer, Werner
Abstract: The islet amyloid polypeptide (IAPP) is a peptide hormone that is secreted by pancreatic beta cells along with glucagon and insulin. The development of type‐2 diabetes mellitus (T2DM) is accompanied by aggregation and amyloid deposits of IAPP. Here we report pressure‐induced changes of NMR chemical shifts for the elucidation of conformational substates of IAPP in bulk solution. Comparison with a similar peptide, the Alzheimer peptide Aβ, reveals that the area around amino acid residues 3–20 displays large differences in the first and second order pressure coefficients, pinpointing to a different structural ensemble in this sequence element, while the area around amino acid residues 28–37 displays similar transient structural conformations for both peptides. Knowledge of the structural nature of the highly amyloidogenic IAPP and the differences with respect to the conformational ensemble of Aβ will help facilitate the rational design of drugs for therapeutic treatment of T2DM. Abstract : Here we report pressure‐induced changes of NMR chemical shifts for the elucidation of conformational substates of IAPP in bulk solution. Knowledge of the structural nature of the highly amyloidogenic IAPP and the differences with respect to the conformational ensemble of Aβ(1–40) will help facilitate the rational design of drugs for therapeutic treatment of T2DM.